The Analysis of Relationship Between Student Bullying Behavior and Student Spiritual Intelligence - Sudirman, Sudirman; Puspita Sari , Susi; Ramli , Akhmad; Mahendika , Devin; Salomo Leuwol , Ferdinand (Mudir : Jurnal Manajemen Pendidikan, 2023)
Every year, bullying has become more common. The IQ of a person is one of the variables that affect bullying. The purpose of this investigation is to determine whether there is a link between spiritual intelligence and the likelihood of student bullying behavior. This study combined a cross sectional methodology with a descriptive correlational technique. Cluster random selection was used to choose the sample for this study, which included 100 people. A bullying behavior risk assessment and a spiritual intelligence questionnaire were both employed in this study, and their results were evaluated using chi-square. Out of 100 kids, the findings revealed that 52 percent had poor spiritual intelligence and a high risk of bullying (73 percent), whereas the remaining 48 percent had strong spiritual intelligence and a low risk of bullying (68 percent). A p-value of 0.000 was found from the chi-square analysis, indicating a strong correlation between spiritual intelligence and the likelihood of student bullying behavior.